Implementasi Gender Mainstraiming dalam Konteks Pembangunan: Studi Kasus Keberhasilan Kesetaraan Gender di Filipina tahun 2018 - Okta Dewi (Parahyangan Center for International Studies, 2021)
ABSTRAK Filipina yang dikenal sebagai negara patriarki diera kolonialisme kini menjadi satu-satunya negara yang yang memiliki tingkat kesetaraan gender tertinggi di Asia. Pengembangan kebijakan pemerintah yang berfokus pada peningkatan kesetaraan gender, menjadikan laki-laki dan perempuan memiliki akses yang sama terhadap semua sumber daya. Hal ini menimbulkan pertanyaan tentang implementasi gender mainstraiming yang dilihat dari konteks pembangunan di Filipina dalam menegakkan kebijakan kesetaraan gender. Tulisan ini mengelaborasikan bahwa implementasi konsep gender mainstraiming yang mengintegrasikan perspektif gender ke dalam persiapan, perancangan, penerapan, monitoring dan evaluasi kebijakan, peraturan pelaksanaan dan program pembiayaan, sebagai salah satu kunci keberasilan kesetaraan gender di Filipina. Dalam artikel ini, penulis menjabarkan tiga argumen utama keberhasilan kesetaraan gender di Filipina pada tulisan ini: pertama, diaodpsinya terminologi gender mainstraiming. Kedua, penerapan gender mainstraiming yang dibuktikan dengan dibentuknya beberapa undang-undang peraturan serta program terkait penerapan kesetaraan gender yaitu The Magna Carta of Women (MCW), The Philippine Development Plan for Women (PDPW) 1989-1992, dan The Philippine Plan for Gender-Responsive Development (PPGD) 1995−2025. Ketiga, implementasi gender mainstraiming dibeberapa sektor diantaranya partisipasi ekonomi dan peluang, pencapaian pendidikan, kesehatan dan kelangsungan hidup, dan pemberdayaan politik. Keseiusan dan kesadaran tinggi pemerintah mengenai pentingya kesetaraan gender konteks pembangunan dituangkan dalam perturan serta undang-undang sebagai kunci yang kemudian diimplementasikan disegala kebijakan. Dalam penjabarannya, penulisan ini akan menggunakan metode penelitian kualitatif dengan bersumber pada data sekunder. Kata Kunci: Kesetaraan gender, perempuan & pembangunan, gender mainstraiming, Filipina ABSTRACT The Philippines, which is known as a patriarchal country in the era of colonialism, is now the only country that has the highest level of gender equality in Asia. Development of government policies that focus on improving gender equality, giving men and women equal access to all resources. This raises questions about the implementation of gender mainstreaming seen from the context of development in the Philippines in enforcing gender equality policies. This paper elaborates that the implementation of the concept of gender mainstreaming which integrates a gender perspective into the preparation, design, implementation, monitoring and evaluation of policies, implementing regulations and financing programs, is one of the keys to the success of gender equality in the Philippines. In this article, the author outlines three main arguments for the success of gender equality in the Philippines in this paper: first, the diodection of the terminology of gender mainstreaming. Second, the implementation of gender mainstaking as evidenced by the formation of several laws and programs related to the implementation of gender equality, namely The Magna Carta of Women (MCW), The Philippine Development Plan for Women (PDPW) 1989-1992, and The Philippine Plan for Gender- Responsive Development (PPGD) 1995-2025. Third, the implementation of gender mainstreaming in several sectors including economic participation and opportunities, educational attainment, health and survival, and political empowerment. The seriousness and high awareness of the government regarding the importance of gender equality in the development context is outlined in regulations and laws as keys which are then implemented in all policies. In the elaboration, this paper will use qualitative research methods sourced from secondary data. Keywords: Gender Equality, women & Development, Gender Mainstraiming, Philippines